Expert Commentary: The Urge to Merge in the Pharmaceutical Industry - Whittington, R (2001)
The economics of mergers are doubtful — we know that more broadly, and the case indicates the same in the pharmaceutical industry specifically. Yet still big businesses strive to get bigger. We should look more widely than to economics for our explanations.